Diagnostic values of MMP-9 and TGF-1β in assessing the severity of liver fibrosis and the rate of its progression in patients with chronic hepatitis C GT 1 infection - Venytska, H. V.; Riabokon, O. V.; Riabokon, Yu. Yu.; Shcherbyna, R. O. (Zaporozhye Medical Journal, 2023)
Aim. The purpose of our work is to find out diagnostic values of serum MMP-9 and TGF-1β determination for assessing the severity of liver fibrosis and the rate of its progression in patients with chronic hepatitis C genotype 1 (CHC GT1) infection. Materials and methods. 92 patients with CHC GT1 were examined. The severity of liver fibrosis was assessed by elastometry. The rate of liver fibrosis progression was calculated using the T. Poynard formula. Serum levels of TGF-1β and MMP-9 were measured by ELISA method. Results. In patients with CHC GT1, the most noticeable changes in the serum parameters of fibrogenesis / fibrinolysis were observed in the presence of F 3–4. The probability of liver fibrosis stages F 3–4 was high at the serum levels of TGF-1β >12.03 pg/ml (p < 0.001), MMP-9 ≤987.20 pg/ml (p = 0.016), TGF-1β/MMP-9 ratio >0.011 (p < 0.001). Fast liver fibrosis progression was more often registered in F 3–4 than in F 0–2 (62.9 % vs. 16.7 %, p < 0.0001). Increasing rate of liver fibrosis progression in these patients was confirmed by a higher ratio of TGF-1β/MMP-9 compared to that in patients with a slow rate of liver fibrosis progression (p < 0.05). The probability of fast liver fibrosis progression was high at the serum levels of TGF-1β >8.69 pg/ml (p < 0.001), MMP-9 ≤920.65 (p = 0.005), TGF-1β/MMP-9 ratio > 0.011 (p < 0.001). Conclusions. The diagnostic value of MMP-9 and TGF-1β in assessing the liver fibrosis severity and the rate of its progression in patients with CHC GT1 has been defined. Cut-off levels of MMP-9, TGF-1β and the TGF-1β/MMP-9 ratio for stratification of patients with severe liver fibrosis and the fast rate of its progression have been proposed.